2020
DOI: 10.1016/j.compositesa.2020.106042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of laminated bamboo under off-axis compression

Abstract: To investigate the compression performance of laminated bamboo, 210 laminated bamboo specimens were tested using seven different lamination angles. Six failure types were classified. All the specimens experienced elastic stage at the beginning of the loading process and then elastic-plastic stage.At the end of the elastic-plastic stage, specimens of 15°, 30°and 45° immediately reached the ultimate bearing capacity, showing brittle failure, while other specimens entered a longer plastic stage before failure.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…When the oil heat-treated temperature is higher than 140 °C, the bending strength increases first and then decreases. The bending strength of the bamboo samples increase by 8.46%, 19.26% and 17.25%, respectively, after oil heat treatment at 160, 180 and 200 °C for 2 h. At the beginning of oil heat treatment, the moisture content at the fiber saturation point decreases, and the dimensional stability improves, resulting in the increase of the bending strength [52,53]. At the same temperature, the bending strength decreases with the time increasing, and it is mainly due to the degradation of chemical components including cellulose and hemicellulose.…”
Section: Effect Of Oil Heat Treatment On Physical and Mechanical Properties Of Bamboomentioning
confidence: 99%
“…When the oil heat-treated temperature is higher than 140 °C, the bending strength increases first and then decreases. The bending strength of the bamboo samples increase by 8.46%, 19.26% and 17.25%, respectively, after oil heat treatment at 160, 180 and 200 °C for 2 h. At the beginning of oil heat treatment, the moisture content at the fiber saturation point decreases, and the dimensional stability improves, resulting in the increase of the bending strength [52,53]. At the same temperature, the bending strength decreases with the time increasing, and it is mainly due to the degradation of chemical components including cellulose and hemicellulose.…”
Section: Effect Of Oil Heat Treatment On Physical and Mechanical Properties Of Bamboomentioning
confidence: 99%
“…The stiffness of the GO nano-platelets can be formulated with five elastic parameters, which are illustrate as below: The stiffness tensor for GO nano-platelets can be demonstrate as equation 31. This equation is based on Hill's elastic coefficients [67]. And:…”
Section: Stiffness Analysismentioning
confidence: 99%
“…Mahdavi et al [26] found that the stiffness of LBL was comparable to that of wood, showing that LBL can be used in building structures. Yang et al [27] studied the off-axis compressive performance of LBL and examined the applicability of the commonly used strength criteria on LBL. Karyadi et al [28] investigated the mechanical properties of box-section LBL beams with different sidewall thickness and found that the strength of the beam significantly increased with the increase of the sidewall thickness.…”
Section: Introductionmentioning
confidence: 99%